Exploring the neural correlates of balance and exercise in dementia - Bajwa, Rupinder Kaur (2023)
Balance deficits in dementia are linked to increased falls risk, leading to injury, fear of falling, reduced activity, and loss of independence. Exercise based interventions can be useful in reducing falls risk as well as improving balance in older adults with cognitive impairments. The neural mechanisms involved in balance and exercise in this population are not well understood. The National Institute for Health Research (NIHR) funded Promoting Activity Independence and Stability in Early Dementia (PrAISED2) Randomised Controlled Trial (RCT), is trialling a tailored exercise programme aimed to promote activity, independence, and stability in older adults with Mild Cognitive Impairment (MCI) and mild dementia. This trial presented a unique opportunity to pilot a novel Virtual Reality (VR) based balance task and investigate the neural correlates of balance in older adults with MCI and dementia. To do this, I used functional Magnetic Resonance Imaging (fMRI) a non-invasive neuroimaging technique which detects haemodynamic changes associated with neural activity at rest or during experimental tasks.